Contemporary issues in housing design - Guler, Kutay (Cambridge Scholars Publishing, 2018)
The word 'house' has evolved throughout the millennia and infused itself into many languages; however, the basic reference to covering and sheltering has always been preserved. Housing in the contemporary sense refers to a relatively complex structure comprising different shapes and sizes accommodating various functionalities, evolving in accordance with cultural, social, technological, and natural progresses. A house provides more than basic protection, but is the backdrop for the daily lives of occupants, and even a reflection of an individual's character, beliefs, and socioeconomic status. T.